Value of intralesional and perilesional radiomics for predicting the bioactivity of hepatic alveolar echinococcosis - Zhang, Simiao; Hou, Juan; Xia, Wenwen; Zhao, Zicheng; Xu, Min; Li, Shouxian; Xu, Chunhui; Zhang, Tieliang; Liu, Wenya (Frontiers in Oncology, 2024)
Objectives: To investigate the value of intralesional and perilesional radiomics based on computed tomography (CT) in predicting the bioactivity of hepatic alveolar echinococcosis (HAE). Materials and Methods: In this retrospective study, 131 patients who underwent surgical resection and diagnosed HAE in pathology were included (bioactive, n=69; bioinactive, n=62). All patients were randomly assigned to the training cohort (n=78) and validation cohort (n=53) in a 6:4 ratio. The gross lesion volume (GLV), perilesional volume (PLV), and gross combined perilesional volume (GPLV) radiomics features were extracted on CT images of portal vein phase. Feature selection was performed by intra-class correlation coefficient (ICC), univariate analysis, and least absolute shrinkage and selection operator (LASSO). Radiomics models were established by support vector machine (SVM). The Radscore of the best radiomics model and clinical independent predictors were combined to establish a clinical-radiomics Nomogram. Receiver operating characteristic curve (ROC) and decision curves were used to evaluate the predictive performance of the nomogram model. Results: In the training cohort, the area under the ROC curve (AUC) of the GLV, PLV and GPLV radiomic models was 0.774, 0.729, 0.868, respectively. GPLV radiomic models performed best among the three models in training and validation cohort. Calcification type and fibrinogen were clinical independent predictors (p＜0.05). The AUC of the nomogram model based clinical and GPLV radiomic signatures was 0.914 in training cohort and 0.833 in validation cohort. The decision curve analysis showed that the nomogram had greater benefits compared with the single radiomics model or clinical model. Conclusion: The nomogram model based on clinical and GPLV radiomic signatures show the best performance in prediction of the bioactivity of HAE. Radiomics including perilesional tissue can significantly improve the prediction efficacy of HAE bioactivity.